Revisão sistemática da literatura sobre invasões biológicas com macrófitas e fatores abióticos relacionados à invasividade da PoaceaeUrochloa arrecta - Evangelista, Heloisa Beatriz Antoniazi (2014)
Riparian vegetation exerts control on ecosystem functioning, especially in the reduction of solar radiation, and limiting the primary productivity in rivers and streams in the most intense way. In addition, riparian areas represent areas of great biological, physical and chemical exchanges between the terrestrial and aquatic environment. The reduction of shading by riparian vegetation, may trigger increased growth of weeds, and can make this region more susceptible to invasion by exotic species. This study highlights the exotic invasive emergent macrophyteUrochloaarrecta in Brazil, which is easily found in degraded environments, probably due to their high dispersal ability through fragments, and high aggressivity in colonizing new environments. In general, we study if the success of U. arrecta and two native species are directly related to the availability of light in the environment. In both studies, it was concluded that the shading by riparian vegetation is a medium to long-term control of this invasive alien species. Finally, the best way to avoid the negative impacts of non-native species is to prevent their introduction, since the high invasive potential of U. arrecta and the loss of diversity of aquatic plants in environments that this species invades, should be taken into consideration for the conservation and maintenance of ecosystem functioning.